Process Evaluation of the Residential Substance Abuse Treatment (RSAT) Program at the South Idaho Correctional Institution, 1999-2000 - Stohr, Mary K. ([Verlag nicht ermittelbar], 2003)
This study is a process evaluation of a Residential Substance Abuse Treatment (RSAT) program at the South Idaho Correctional Institution (SICI), addressing the following research questions: (1) Did the SICI RSAT program as delivered conform with its stated goals and objectives? (2) Did the program result in reduced recidivism, abstinence from drug and alcohol use, and reduced costs of incarceration? (3) Did the referral process identify the targeted population? (4) Would the SICI RSAT data, management, staffing, and design be suitably established within two years to allow for a full outcome evaluation? (5) Were there communication issues among the IDOC, Parole Commission, and contract providers that might interfere with program implementation and delivery? and (6) Were there any cooperative remedies that had been, or might be developed to address implementation and delivery difficulties? Researchers conducted field observations (Part 1, Observational Data) of program delivery by program leaders using both the Cognitive Change Program Module and the Minnesota Model-Based Chemical Dependency Treatment Modules in each of the three phases of the therapeutic community environment. Researchers administered questionnaires to inmates (Part 2, Inmate Interview Data) and staff (Part 3, Staff Interview Data) regarding their perceptions of program operations. Variables for Part 1 include the date and time of observation, nature of observation, clarity, organization, and substance of program delivery, the program leader's involvement and the quality of that involvement with inmates, how prepared the program leader was, and the general therapeutic atmosphere of the program. Demographic variables for Part 2 include the race, age, ethnicity, and level of education of each inmate. Other variables include use of alcohol and illegal drugs prior to incarceration, inmates' perceptions of the treatment personnel, their levels of involvement with the group meetings and cognitive self-change groups, the atmosphere of therapy, ratings of communication and delivery of treatment, quality of service, and the strengths and weaknesses of the RSAT program. Variables for Part 3 include staff's perceptions of the RSAT program and whether they felt the program content and delivery were well organized and easy to understand, perceptions of the program leader's preparation and involvement, perceptions of communication and consistency issues, the quality of service, and the strengths and weaknesses of the RSAT program.